Pertumbuhan dan kelangsungan hidup ikan nila Oreochromis niloticus yang dikultur pada sistem akuaponik dengan kepadatan biofilter kangkung yang berbeda - Gerung, Pramulya R.A; Mudeng, Joppy D.; Salindeho, Indra R.N.; Longdong, Sammy N.J.; Pangkey, Henneke; Rumengan, Inneke F.M. (Universitas Sam Ratulangi, 2022)
This research was conducted to determine the optimal density of kale plants as biofilter in an aquaponic system that can trigger the highest growth and survival of tilapia. The experiment was designed in a completely randomized design (CRD) with 3 treatments and 3 replications so that there were 9 experimental units. The factor tested was the different density of kale plants as biofilter in the aquaponics system, where treatment A: 6 kale plants/0,24m2, B: 12 kale plants/0,24m2, and K: without kale plants (as control). This study was conducted for 28 days. Collected data included weight, length and number of fish, which were then converted to absolute growth rate (weight and length) , daily growth rate, survival rate and kale plant growth. Data were analyzed using ANOVA and then Least Significance Differences (LSD) for further analysis. The results showed that the different density of kale plants had no significant effect on absolute growth rate (weight and length) and daily growth rate, but had a significant effect on the survival rate of fish. The LSD results showed that density of 6 kale plants/0,24m2 (A) were not significantly different from that of 12 individuals kale plants/0,24m2 (B), but both treatments were significantly different from the control (K). The range of ammonia was between 0.29 – 0.91 mg/l, nitrite 0.55 – 1.06 mg/l, and nitrate 10 - 47 mg/l.